Ciris : A Poem from the Appendix Vergiliana - Kayachev, Boris (Classical Press of Wales, The, 2020)
Cover -- Title Page -- Table of Contents -- Preface -- Introduction -- Date of Composition and Authorship -- Manuscript Transmission and the Text -- Text and Critical Apparatus -- Translation -- Commentary -- Bibliography -- General Index -- Index of Greek and Latin Words -- Index of Passages Discussed.